2023
DOI: 10.1097/hep.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

IgY antibodies against cytolysin reduce ethanol-induced liver disease in mice

Abstract: Background and Aims: Patients with severe alcohol-associated hepatitis have high morbidity and mortality. Novel therapeutic approaches are urgently needed. The aims of our study were to confirm the predictive value of cytolysin-positive Enterococcus faecalis (E. faecalis) for mortality in patients with alcohol-associated hepatitis and to assess the protective effect of specific chicken immunoglobulin Y (IgY) antibodies against cytolysin in vitro and in a microbiota-humanized mouse model of ethanol-induced live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To identify fungal genera and species with the highest feature importance for detecting ALD vs NAFLD, we determined the mean decrease accuracy per random forest analysis, as described before. 32 , 33 Among the top genera differentiating ALD from NAFLD were Scopularopsis , Kluyveromyces , unidentified genera, Mucor , Saccharomyces , and Kazachstania ( Figure 2a ). Among the fungal species with the highest feature importance for detecting ALD vs NAFLD were S. cordiae , M. restricta , unknown species, S. cerevisiae , and C. albicans ( Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify fungal genera and species with the highest feature importance for detecting ALD vs NAFLD, we determined the mean decrease accuracy per random forest analysis, as described before. 32 , 33 Among the top genera differentiating ALD from NAFLD were Scopularopsis , Kluyveromyces , unidentified genera, Mucor , Saccharomyces , and Kazachstania ( Figure 2a ). Among the fungal species with the highest feature importance for detecting ALD vs NAFLD were S. cordiae , M. restricta , unknown species, S. cerevisiae , and C. albicans ( Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“… 31 Area under the curve (AUC), best threshold to maximize the Youden index, sensitivity, specificity, accuracy, positive predictive value, negative predictive value, and p value between two AUCs of receiver operating characteristic (ROC) curves per DeLong method were calculated using the pROC library in R; and to identify fungal genera and species with the highest feature importance for detecting ALD cohorts vs NAFLD cohorts, the mean decrease accuracy was calculated with the randomForest library in R, as described. 32 , 33 Statistical analysis was performed using R statistical software, R version 1.3.1093 for Mac, 2020 the R Foundation for Statistical Computing.…”
Section: Methodsmentioning
confidence: 99%
“…The abundance of fecal cytolysin-positive E. faecalis correlates with the severity of liver disease in patients with alcohol-associated hepatitis. Bacteriophages targeting cytolytic E. faecalis as well as IgY antibody administration against cytolysin attenuate experimental ethanol-induced liver disease [46,47]. Fecal cytolysin did not predict disease severity in patients with liver cirrhosis and acute decompensation and in patients with acute on chronic liver FIGURE 2.…”
Section: Alcohol-associated Liver Diseasementioning
confidence: 96%
“…2023, 6, 107 2 of 12 recently emerged as compelling candidates with potential clinical implications [9]. Recent studies [9,10] observed an increased relative abundance of E. faecalis in the feces from patients with alcohol-associated hepatitis, specifically a strain that secretes the exotoxin cytolysin. The presence of cytolysin-positive E. faecalis correlated with the severity of liver disease and mortality rate in patients with alcohol-associated hepatitis [9].…”
Section: Introductionmentioning
confidence: 99%